Anatomy of What We Value Most - Gerber, William, (Value Inquiry Book Series ;, 1997)
The book analyzes, synthesizes, and evaluates the insights of the world's outstanding thinkers, prophets, and literary masters on the good, the morally right, and the lovely (part one); the question whether the world operates on the basis of such universal laws as the logos, the tao, and the principle of polarity (part two); what there is and isn't in the world, including such categories as existence, reality, being, and nonbeing (part three); and pre-eminently credible and enriching beliefs about truth, wisdom, and what it all means (part four). Emphasis is placed on the divergent views of such intellectual giants as Confucius and Laotse in ancient China; the classical Hindu philosophers from ancient times to Gandhi and Tagore; patriarchs and prophets quoted in Scripture; Socrates, Plato, and Aristotle; Saints Augustine and Thomas Aquinas in the Middle Ages; Descartes, Spinoza, Locke, Hume, and Kant; and nineteenth- and twentieth-century luminaries such as Bentham, Mill, Peirce, James, Dewey, Sartre, and Wittgenstein. The differences and resemblances of their cogitations are portrayed as a conversation of the ages on questions of persistent concern.